The CSR Perception of Front-line Employees of Luxury Fashion Businesses - Macgregor Robert K. (Organizacija, 2020)
Background and Purpose: The sustainability projected into Corporate Social Responsibility (CSR) is pivotal for luxury fashion businesses and they heavily refer to it. However, do their front-line employees follow this trend? To achieve an effective and efficient CSR, the front-line employees have to share the CSR perception advanced by their businesses. The main objective of the study is to discover, critically assess and compare the CSR perception of the front-line employees of the top luxury fashion industry businesses located in Prague, Czech Republic.